Interaction of thermal radiation in hydromagnetic viscoelastic nanomaterial subject to gyrotactic microorganisms - Waqas, M.; Khan, M. Ijaz; Hayat, T.; Farooq, S.; Alsaedi, A. (Applied nanoscience, 2019)
Importance of solar energy in human society cannot be ignored. Electricity, water, and heat can be achieved from solar power. Sustainable energy formation nowadays is a serious issue in the development of human society. Solar energy is deliberated as one of the greatest sources of renewable energy. This energy is 2000 times larger than the utilization of human society. Thus the intention here is to address the impact of gyrotactic microorganisms on two-dimensional (2D) stratified flow of Jeffrey nanomaterial. Applied magnetic field along with mixed convection is considered in the formulation process. Theory of microorganisms is utilized just to stabilize the suspended nanoparticles through bioconvection which has been induced by combined effects of buoyancy forces and magnetic field. Convergent series solutions for the obtained nonlinear differential systems are derived. Impacts of different emerging parameters on velocity, temperature, concentration, and motile microorganisms’ density are addressed through graphs. Numerical values for the local Nusselt, Sherwood and density number of motile microorganisms are computed and analyzed. It is observed that thermal, concentration, and motile density stratification parameters result in the reduction of temperature, concentration, and motile microorganisms’ density distributions, respectively.